Caracterização da estrutura sócio-genética de uma população de vida livre de cachorro vinagre (Speothos venaticus) (Lund, 1842) - Barragán Ruiz, Carmen Elena (Universidade Federal de São Carlos, 2016)
Whereas the S. venaticus, has a wide distribution, estimated from Panama to northern Argentina, the dog vinegar is considered "near threatened" by the IUCN and "Vulnerable (VU)" by MMA. The molecular and biological data deficiency of this species is due mainly to the difficulties of capturing and observing natural environments, indicating a decline in population density of the species. Therefore, the objectives of this study were to determine the socio-genetic structure of family groups of S. venaticus, as well as estimate of kinship and population parameters such as genetic diversity and population structure, comparing parameters of genetic diversity between representatives of nature and captivity. For this, we used 12 microsatellite genetic markers, three specific primers and nine heterologous originally described for Canis familiaris and mitochondrial marker (CR - d-loop). They were obtained 38 blood samples of these, one 23 from the sample bank of CENAP/ICMBio, samples from the municipalities of N. Xavantina and Água Boa (MT), located of north the Mortes’s river, a place with great agricultural exploitation, reducing the closed portion by human actions. The nine heterologous loci showed a PIC> 0,6. Average values of observed heterozygosity (Ho) by codominant markers indicated a deficiency in the captive population, while haplotype diversity of data were the same for both populations. Diversity of data and allelic richness when compared to both populations showed a low for the captive population. Analysis of population structure, estimated a FST 0,165 between populations. Kinship analysis, suggested that 23.8% of individuals in the population in situ. However, also point out the need to expand the number of individuals sampled and conduct a follow-up field to elucidate the issues that emerged from this study.
Keywords: Genética; S. venaticus; Marcadores genéticos; População; OUTROS